Manual de procedimientos para el área de recepción del hotel pirámide en la ciudad de Machala. - Cajamarca Duran, Felipe Esteban (My University, 2018)
El Oro province, on these days has an excelent economical movement, which allows the needings of hotel services, specially on Machala city, this concern motivates to develops this proyect, focused to realice a general diagnostic of the reality of the administration for the Hotel Piramide, which is located on the periphery of the city in the north sector. The diagnosis will evidence the needings of giving a better attention to the users, and whie elaborating the manual of procedures, ti will determinate the fullfillment of quality standars for the activities on reception área in the hotel, the metodology of investigation will be of qualitative focus with an analitic reaching, extracting information for interviews and surveys aplieds to the internal and external clients. The working enviroment should be treated as an importance factor to give a better service and position the hotel into the best qualification that the Tourism Ministery gives into their clasification.
La provincia de El Oro, en la actualidad tiene un excelente movimiento económico que permite la necesidad de servicios hoteleros especialmente en la ciudad de Machala, este referente motiva a desarrollar este trabajo enfocado a realizar un diagnóstico general de la realidad administrativa del servicio que brinda el Hotel Pirámide que está ubicado en el casco de la ciudad sector norte. El diagnostico permitirá evidenciar las necesidades de brindar una mejor atención al usuario y al elaborar el manual de procedimientos se determinará el cumplimiento de estándares de calidad en las actividades del Área de Recepción del Hotel, la metodología de investigación será de enfoque cualitativo con un alcance analítico para extraer información de entrevistas y encuestas aplicada al cliente interno y externo. El clima laboral debe ser tratado como un factor de importancia para brindar un mejor servicio y posicionar al Hotel dentro de las mejores calificaciones que otorga el Ministerio de Turismo en su clasificación.
Keywords: MANUAL; HOTEL; PROCESOS; RECEPCIÓN